The Influence Of Self Efficacy and Locus Of Control On Employee Performance Through Learning Agility at PT. Pegadaian in Cirebon - Rachman, Nisa; Ningsih, Imas Ayu; Hartono, Edy (CV. AFDIFAL MAJU BERKAH, 2025)
Learning agility and its impact on performance at PT Pegadaian are the focus of this study, which aims to investigate the function of self-efficacy and locus of control in this context. There were no exceptions among the 120 workers; everyone was actively engaged. Results showed a favorable correlation between high levels of self-efficacy and better performance. In a similar vein, having an internal locus of control helps one function at their best. The link between self-efficacy, locus of control, and employee performance was strengthened by learning agility, a major mediating variable. To overcome the impact of these two mental aspects on productivity on the job, people's capacity for rapid and flexible learning is crucial. As a result, boosting employees' learning agility and positive self-efficacy may work hand in hand to boost their performance. This study investigates the mediating role of learning agility in the relationship between self-efficacy, locus of control, and employee performance at PT. Pegadaian in Cirebon. A total of 120 employees participated in the study using a saturated sampling technique. Data were collected through questionnaires and analyzed using SPSS 25. The findings reveal that self-efficacy (β = 1.000, p < 0.000) and locus of control (β = 0.176, p < 0.000) significantly affect employee performance. Learning agility acts as a significant mediator, with a direct effect on performance (β = 0.501, p < 0.000), indicating its pivotal role in enhancing performance through psychological traits. The adjusted R² value of 1.000 supports the robustness of the model. These findings underscore the importance of internal psychological mechanisms and adaptability in achieving high job performance.